Assertive Illocutionary Act Used By Main Character in “The Adam Project” Movie - Putu Arya Sindhu Dhaneswara; Ni Luh Ketut Mas Indrawati; Gusti Agung Istri Aryani (CV. ULIL ALBAB CORP, 2024)
This research discusses the illocutionary acts in the movie entitled The Adam Project. This research focuses on assertive illocutionary acts. This research aims to identify the form of assertive illocutionary acts and know the purpose of the form of illocutionary acts used by the main character. The data source in this research is a movie entitled The Adam Project. The data used in this study are the utterances of the main character that allegedly contain the type of assertive illocutionary acts. This research uses a descriptive qualitative method to analyze and present the data. This research classifies the data based on the theory proposed by Searle (1979). The result of this research is that there are five types of assertive illocutionary acts which include stating, reporting, explaining, asserting, and showing. The five types of assertive illocutionary acts have language variations used by speakers to influence their speech partners by following the truth.